EDUCATION ON INTRODUCTION TO MEDICINE DOSAGE FORMS FOR CHILDREN AT THE KB-TK LEVEL ATPAUD ALAM CAHAYA HASANAH: EDUKASI PENGENALAN BENTUK SEDIAAN OBAT PADA ANAK TINGKAT KB-TK DI PAUD ALAM CAHAYA HASANAH - Cut Suraiya Wahyuni Utami; Resmila Dewi; Rina Kurniaty; Erda Marniza (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
The growth and development of early childhood need to be directed at laying the right foundations for growth and development into a whole human being. Knowledge about the form of drug preparation is very much needed so that using a drug can be effective safely, and efficiently and provide optimal effects. One type of drug preparation form that is often used in children (under 6 years of age) is a solid dosage form (powder). This preparation is intended if the child is unable to consume the drug in the form of a tablet, then it will be formulated in the form of a powdered drug preparation (puyer) so that the drug can be consumed properly and with the right indications, but because this drug dosage form has disadvantages, one of which is the bitter taste of the drug left around the mouth causing nausea and vomiting so that it is rarely liked. Introduction to the form of drug dosage needs to be introduced early to change the views of children who believe that drugs are something that is not pleasant to consume because it causes a bitter taste so they do not want to comply with the rules for using drugs. The conclusion of this community service activity provides information, education, and knowledge so that children are more familiar with the form of drug dosage supported by the screening of videos.